A novel technique in the treatment of post traumatic parotid duct sialocele - Gujrathi, Atishkumar B.; Ambulgekar, Vijayalaxmi (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Stenson’s duct of parotid gland is a major duct which drains saliva into the oral cavity. Deep penetrating wound in the form of cut or crush injury to the buccal area carries the risk of parotid duct injury. It is in the form of ductal exposure, laceration, total severing, or crushing of the duct. These conditions are difficult to diagnose because of complex anatomy and variable nature of injury. Successful management of parotid duct injury depends on early diagnosis and appropriate intervention, failing of which may lead to complications like sialocele or salivary fistula. Many techniques have been proposed for diagnosis and management of parotid duct injuries. This article presents an easy and an innovative technique to diagnose and manage the parotid duct injuries using an "epidural catheter" which is often used for inducing spinal anesthesia. The technique of epidural catheter usage, its advantages, and limitation over other techniques proposed for the management of parotid duct injury are discussed.